The Effect of Digital Talent on Individual Innovation Behavior, Skills of Revolution Industry 4.0 as Mediator Variables - Riri Nofrita; Insannul Kamil; Jonrinaldi Jonrinaldi; Berry Yuliandra; Irsyadul Halim (Jurnal Optimasi Sistem Industri, 2020)
In the face of the Revolution industry 4.0, global connection, artificial intelligence, and automation have disrupted technology. This made the industrial world's development in work competition, not linear and even created new jobs. Digital talent and innovation are needed to face the world of work. This study discusses the construct effect between digital talent, individual innovation behavior, and Skills Revolution Industry 4.0, and the effect of Skills Revolution Industry 4.0) as a mediator to digital talent constructs' relationship. Data collection is obtained directly (face to face).  Samples were previously clustered by sampling technique. Questionnaires use the Likert Scale. Then, the data gotten were processed by SEM-PLS with Software 3.8.2. The result showed that digital talent has a positive effect on individual innovation behavior. This meant that skill of revolution industry 4.0 as a construct mediator was successful. The stronger digital talent influences, the stronger individual innovation behavior influences, and it is accelerated with revolution industry skills 4. This study proposes a model to build mastery of digital talent and individual innovation behavior of Universitas Andalas students through the mastery of skills of revolution 4.0 as a mediator. This research can pave the way to improve students' readiness in facing the world of revolution 4.0, one of which is in the field of digital innovation.